POWER DISTANCE IN UNIVERSITY ENVIRONMENT, PERCEIVED BY AUSTRALIAN AND VIETNAMESE STUDENTS = Khoảng cách quyền lực trong môi trường đại học, tiếp nhận bởi sinh viên Úc và sinh viên Việt Nam - Trần, Quốc Trung (2020)
The development of mankind history requires international, thus intercultural communication. Among such communication, Power distance, one of six cultural dimensions introduced by Hofstede, has been playing the role in showing how societies handle unequal distribution of power. Since there has been little research on this in Vietnam, this paper was carried out to investigate power distance manifestation in the university environment, taking undergraduate students from Vietnam and Australia as research participants. Hopefully, the research would be a source of reference for students and teachers of English in general and cultural studies in particular. Qualitative research design was applied to discover the manifestation of power distance by students from University of Languages and International Studies VNU (Vietnam) and Swinburne University of Technology, Melbourne (Australia). Fifty students from both countries were chosen to take part in the research, which purposive sampling method was utilized. Structured questionnaire of 20 questions and semi-structured interview were employed to collect data, studying two main aspects namely group work and classroom environment; meanwhile, content analysis was the main data analysis method. The findings indicated that Australian students were likely to behave in low power distance way in both group work and classroom atmosphere; whereas, Vietnamese students only followed high power distance behaviors in classroom environment while they manifested low power distance behaviors in group work. This finding suggests that students who schedule for overseas study should understand beforehand the working style of targeted environment. In addition, teachers are also advised to be careful with their foreign student evaluation, and should also negotiate working style with their students in the first lesson.